Migration and Integration of Foreign Priests. Aspirations, Religiosity, and Tensions in the Narratives of Foreign Priests in Italy - Delli Paoli, Angela; Masullo, Giuseppe (Qualitative Sociology Review, 2023)
This paper aims to understand the individual factors sustaining the migratory flow of Catholic priests to Italy. Priests’ migration cannot be seen as the mere result of lack of vocations and shortage of priests in the host country since their agency, belief, aspirations, and motivations affect their religious identity and, consequently, their integration and participation in the host country. Drawing on qualitative research, this paper collects the voices and the narratives of selected international priests living in Italy. Priests’ interviews led to broad-range questions about the nature of migration decisions and their integration into the host society and churches that originate from differences in religiosity, vocations, and missions. That resulted in a typology of 4 types of migrant priests: careerist priests, highly educated and integrated into the host country, driven by career and salary aspiration, and showing a highly politicized vision of religion; servant priests, with a strong missionary impulse to serve the Church as a universal institution transcending abstract and real boarders; evangelist priests who feel the moral obligation to evangelize secularized countries to bring them back to the origins of Catholicism; rebel priests who feel second-class priests, discriminated both within and outside the Church, in a country where they were forced to move, for this reason questioning their sense of clear vocational directions.